Time-dependent nonuniform numerical model of corrosion process and consequent corrosion-induced concrete cracking under chloride attack. (June 2023) - Bui, Huy Tang; Tan, Kang Hai
Abstract: Corrosion of steel bars and consequent concrete cracking are complicated processes and they mutually affect one another. In this study, a 3D time-dependent numerical model was developed to simulate localised corrosion in both circumferential and longitudinal directions, incorporating effects of nonuniform corrosion-induced cracks. Time-dependent evolution of corroded area in the circumferential direction around the steel bar was calculated as a function of chloride concentration, while two configurations of corroded length along the steel bar axis were simulated: (1) the entire length of steel bar was corroded at the same time and (2) the corroded length progressively developed from the middle of the bar towards its two ends. Microcell and macrocell mechanisms were applied to determine the total corrosion rate. Consequently, a finite element model was developed to simulate nonuniform corrosion-induced concrete cracking. It was found that once a vertical crack propagated through the concrete cover, not only did the corroded area spread faster, microcell and macrocell current densities also substantially increased, and the shape of corroded depth became more rounded.